<span>y-2x=-6 and 5x-y=9
step 1: isolate y in the first equation
y = 2x - 6
step 2: substitute the y value on the 2th equation:
5x-(2x-6)=9
step 3: solve the present equation:
5x - 2x + 6 = 9
3x = 9-6
3x = 3
x = 1
step 4: get the y value by replacing the value of x in </span>y = 2x - 6:
<span>
y = 2*1 - 6
y = 2 - 6
y = -4
S={1, -4}
</span>
Answer:
d
Step-by-step explanation:
Volume- LxWxH
30x10x50= 15000
Rectangle. I hope this helps.
Yes. The numerator does not increase as fast as the denominator increases, causing the function's value to decrease with every subsequent increase in the value of k. This causes the function to converge at a point.